VOLUNTARY DISCLOSURE SEBAGAI PEMODERASI PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Wiguna, I Putu Indra; Putri, I G. A. M. Asri Dwija (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
The purpose of this study was to test the effect of the Corporate Governance Perception Index scores in the company's value and its influence when considering the Voluntary Disclosure as a moderating. The population was a company registered in the Corporate Governance Perception Index (CGPI) and listed on the Indonesia Stock Exchange in 2010-2014.sampling technique use purposive sampling, 30 companies was chosen as the sample. The data analysis technique used is a metode multiple linear regression analysis with the method Moderated Regression Analysis (MRA). The results provide evidence that the CGPI no significant effect on the value of the company. Analysis of moderating variables by using MRA showed that the Voluntary Disclosure is a moderating variable between CGPI relation to the value of the company.
Keywords: CGPI, Firm Values, Voluntary Disclosure